Dielectric materials for energy storage and energy harvesting devices - Rajput, Shailendra; Parida, Sabyasachi; Sharma, Abhishek (Robotics engineer); Sonika, Sonika (River Publishers, 2023)
As the demand for energy harvesting and storage devices grows, this book will be valuable for researchers to learn about the most current achievements in this sector. Sustainable development systems are centered on three pillars: economic development, environmental stewardship, and social. One of the ideas established to achieve balance between these pillars is to minimize the usage of nonrenewable energy sources. Harvesting energy from the surrounding environment and converting it into electrical power is one viable solution to this problem. In recent years, there has been a surge in the development of new energy generation technologies such as solar, wind, and thermal energy to replace fossil fuel energy supplies with cleaner renewable ones. Energy harvesting systems have emerged as a key study topic and are rapidly expanding. Technical topics discussed in the book include: ⁰́Ø Polymer nanocomposites ⁰́Ø Nanomaterials ⁰́Ø Multiferroic properties ⁰́Ø Synthesis of dielectric materials ⁰́Ø Energy harvesting technologies.
Keywords: Energy harvesting -- Materials.; Energy storage -- Materials.; Dielectric devices.; elektronické knihy; electronic books